2021
DOI: 10.3390/ijms23010119
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fullerenol C60(OH)36 on the Antioxidant Defense System in Erythrocytes

Abstract: Background: Fullerenols (water-soluble derivatives of fullerenes), such as C60(OH)36, are biocompatible molecules with a high ability to scavenge reactive oxygen species (ROS), but the mechanism of their antioxidant action and cooperation with endogenous redox machinery remains unrecognized. Fullerenols rapidly distribute through blood cells; therefore, we investigated the effect of C60(OH)36 on the antioxidant defense system in erythrocytes during their prolonged incubation. Methods: Human erythrocytes were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The C 60 nanofilm increased the expression of catalase in peroxisomes, in particular in HepG2 cells. Grebowski et al [52] reported similar results: hydroxyfullerene C 60 (OH) 36 at a of 50-150 mg/L increased catalase expression by 24% in human erythrocytes incubated for 3 and 48 h and subjected to oxidative stress. The authors explained that the mechanism of action of the fullerene derivative involves a conformational change of catalase, which protects the -SH groups against ROS-induced oxidation.…”
Section: Discussionmentioning
confidence: 65%
“…The C 60 nanofilm increased the expression of catalase in peroxisomes, in particular in HepG2 cells. Grebowski et al [52] reported similar results: hydroxyfullerene C 60 (OH) 36 at a of 50-150 mg/L increased catalase expression by 24% in human erythrocytes incubated for 3 and 48 h and subjected to oxidative stress. The authors explained that the mechanism of action of the fullerene derivative involves a conformational change of catalase, which protects the -SH groups against ROS-induced oxidation.…”
Section: Discussionmentioning
confidence: 65%
“…Analysis of the influence of ROS must also consider their wide range of influences on biological objects, in particular, the cell membrane. To study oxidative stress, RBCs are often used as a research model [ 34 , 35 ]. Moreover, such analyses must take into account that the most active ROS that influences lipids in RBC membranes is radical [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Electron‐deficient carbon─carbon double bonds and hydroxyl groups can quench numerous electrophilic radicals; [ 13 ] this remarkable reaction to free radicals is the most important property of fullerenols. Moreover, they can enhance intrinsic enzymatic activity and regulate intracellular anti‐oxidative substances, [ 14 ] rendering them attractive antioxidants for various applications. Fullerenols produce radiation‐protective effects on mature human erythrocytes, [ 15 ] alleviate radiation‐induced dermatitis during radiotherapy, [ 16 ] mitigate radiation‐induced duodenal damage, [ 17 ] reduce joint destruction, suppress bone resorption, and stimulate osteogenesis in the bone marrow.…”
Section: Introductionmentioning
confidence: 99%